From inside to outside (and vice versa) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
This contribution will focus on some aspects of the roots of environmental art in Italy, with reference to works created between the 1950s and 1960s by Lucio Fontana, to environments designed by members of Gruppo T and other artists (Giulio Paolini, Luciano Fabro) in the 1960s, and through reflections on the different uses of space that were defined with the exhibition Lo spazio dell’immagine held in Foligno in 1967. The approach is not, however, that of a historical review of well-known events, but of an investigation into the way to understand the relationship between outside and inside, the sense and value of the “passage,” the conception of the modifying factors, starting with light, which have acted on the definition of space as an element to be perceived, rather than a place to be in, emphasising the dynamics that define a dialectical, if not antithetical, relationship with respect to architectural and design qualities in the proper sense, leading to reading the environmental art intervention as an invitation to follow a path.
Keywords: Outside-inside; Light; Grazia Varisco; Gruppo T; Lucio Fontana